2013
DOI: 10.1016/j.immuni.2012.12.003
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Factor 1 Is Required for Group 2 Innate Lymphoid Cell Generation

Abstract: SUMMARY Group 2 innate lymphoid cells (ILC2) are innate lymphocytes that confer protective type 2 immunity during helminth infection and are also involved in allergic airway inflammation. Here we report that ILC2 development required T cell factor 1 (TCF-1, the product of the Tcf7 gene), a transcription factor also implicated in T cell lineage specification. Tcf7−/− mice lack ILC2, and were unable to mount ILC2-mediated innate type 2 immune responses. Forced expression of TCF-1 in bone marrow progenitors parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
244
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(252 citation statements)
references
References 50 publications
4
244
0
Order By: Relevance
“…RBP-Jk deletion selectively decreased IL-22-producing NKp46 + IL-7Ra + ILCs in the lamina propria but not in the Peyer's patches (45). Epigenetic analysis revealed that IL-7Ra expression in ILC2 cells was directly regulated by TCF1, which was shown to be a direct target of the Notch-RBP-Jk pathway in T cells (46,47). In fact, we also found ICN1 binding on the promoter region (231 kb upstream from the TSS) of TCF1 in gd T cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…RBP-Jk deletion selectively decreased IL-22-producing NKp46 + IL-7Ra + ILCs in the lamina propria but not in the Peyer's patches (45). Epigenetic analysis revealed that IL-7Ra expression in ILC2 cells was directly regulated by TCF1, which was shown to be a direct target of the Notch-RBP-Jk pathway in T cells (46,47). In fact, we also found ICN1 binding on the promoter region (231 kb upstream from the TSS) of TCF1 in gd T cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1). Progressive commitment to the ILC lineage is also dependent, to varying degrees, on a multitude of transcription factors including GATA‐3, TOX, TCF‐1 and NFIL316, 17, 18, 19, 20, 21 (and reviewed in detail in references 10 and 22). …”
Section: Group 3 Innate Lymphoid Cell Developmentmentioning
confidence: 99%
“…Interestingly, data indicate that the role of TCF-1 in ILC development is not limited to ILC2 as numbers of RORct ? ILC3 are also reduced in the absence of this TF (Mielke et al 2013;Yang et al 2013).…”
Section: Development and Ontogeny Of Ilc2mentioning
confidence: 95%
“…TCF-1 directly drove Il7r expression, allowing ILC2 responsiveness to this cytokine. Forced TCF-1 expression in bone marrow cells in vitro, however, appears to by-pass the need for Notch signaling as the cells up-regulate many of the factors associated with ILC2 function independently of Notch signaling (Yang et al 2013). Interestingly, data indicate that the role of TCF-1 in ILC development is not limited to ILC2 as numbers of RORct ?…”
Section: Development and Ontogeny Of Ilc2mentioning
confidence: 99%
See 1 more Smart Citation